2007
DOI: 10.1002/pd.1870
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac stroke volume determination by four‐dimensional ultrasound with spatio‐temporal image correlation compared with two‐dimensional and Doppler ultrasonography

Abstract: There is a good agreement between SV measured either by 2D Doppler or by 4D STIC. The 4D STIC represents a simple and rapid technique to estimate fetal SV and promises to become the method of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 13 publications
5
49
1
Order By: Relevance
“…Volume acquisitions followed a previously reported technique 16 starting from the 4-chamber view of the fetal heart as a reference plane. Care was taken to have an angle of insonation of the interventricular septum of approximately 45°.…”
Section: Methodsmentioning
confidence: 99%
“…Volume acquisitions followed a previously reported technique 16 starting from the 4-chamber view of the fetal heart as a reference plane. Care was taken to have an angle of insonation of the interventricular septum of approximately 45°.…”
Section: Methodsmentioning
confidence: 99%
“…Specialized algorithms are applied to the saved STIC volume to measure ventricle volume [13,14,15,16,18,19,20]. This technique can also be extended to obtain ventricle mass [21] (fig.…”
Section: D/4d Us – Spatiotemporal Image Correlationmentioning
confidence: 99%
“…3). 3D/4D US is most often applied to fetal heart functional evaluation with the goal of obtaining ventricular volumes to extrapolate fetal SV (velocity time integral × valve area, a calculation of the volume of blood flow out of the heart at systole), EF (SV/end-diastolic volume), and CO (SV × heart rate) [13,14,15,16,17,18]. Ventricle volumetry may be applied to the evaluation of suspected CHD with disturbance of ventricle size, such as cardiomegaly and cardiomyopathy, stenotic aortic valve and evolving hypoplastic left heart syndrome, or Ebstein anomaly.…”
Section: D/4d Us – Spatiotemporal Image Correlationmentioning
confidence: 99%
“…Moreover, the different techniques have acceptable intra- and interobserver variability [12,13,14,15,16,17]. Different groups have published nomograms for stroke volume and cardiac output, based on relatively large series of healthy fetuses [12,15,16,17]. In the current study, we aimed to evaluate the correlations between the three most commonly used 3D algorithms and the conventional Doppler method for cardiac output measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on validating 3D ventricular volume measurements both in vitro and in vivo and demonstrated that 3D ultrasound volume measurements correspond well to the actual volume. Moreover, the different techniques have acceptable intra- and interobserver variability [12,13,14,15,16,17]. Different groups have published nomograms for stroke volume and cardiac output, based on relatively large series of healthy fetuses [12,15,16,17].…”
Section: Introductionmentioning
confidence: 99%